Hydration measures of Division I collegiate female soccer goalkeepers and field players - Minton D. M.; Torres-McGehee, T. M.; Yeargin S. W.; Rosehart S.; Paper S.; Whittington E.; Sutton K.; Emerson, C. C. (Journal of Athletic Training, 2013)
Much of the hydration research within competitive soccer has utilized male athletes; additionally, goalkeepers (GK) are often excluded from research studies. Although GK do not cover as much distance during practices as field players (FP), they are required to perform high intensity, short duration activities requiring strength, speed, and agility. Objective: To determine hydration measures among female GK and FP during 11 days of pre-season practice. Design: Observational cohort study. Setting: Practice facility of a Division I collegiate female soccer team in the Southeastern United States. Patients or Other Participants: Participants were 17 (3 GK and 14 FP) female collegiate soccer players (age = 19 +1yrs, height = 168.2 +5.9cm, and weight = 63.8 +7.0kg.) Players represented all education levels and FP represented all positions. Intervention(s): All hydration measures were assessed for 11 days (14 practices) during pre- season training. Participants provided a urine sample and weighed pre- and post-practice. Urine was measured for urine specific gravity (Usg) and urine color (Ucol). Weight was measured semi-nude. Volume of fluid consumed (Vfluid) during activity was measured for each player by providing individualized water and carbo-hydrate-electrolyte beverage (CEB) bottles. Practice time was recorded for each practice, from the beginning of warm-up to the end of the cool-down session. Sweat rate (SR) was calculated by using change in body mass and Vfluid. Main Outcome Measure(s): Usg, Ucol, percent change in body mass (%˜BM), SR, Vfluid, and practice time. Repeated measures ANOVAs were used to determine differences in all dependent variables between GK and FPs over the 14 practices. Results: GK practiced significantly more than FP (1.87+0.5hrs vs. 1.69+0.4hrs, P = 0.003). GK consumed similar Vfluid (total = 1.1+0.6L; water = 0.5+0.4L, CEB = 0.7+0.5L) compared to FP (total =1.1+0.6L; water = 0.7+0.6L, CEB = 0.6+0.4L). SR was also similar for both GK and FP (0.7+0.4L/hr and 0.8+0.5L/hr, respectively). There were no significant differences between GK and FP for %˜BM, Usg, or Ucol. Mean pre-practice Usg = 1.020+0.001µG and did not significantly increase postpractice (1.021+0.002µG). Mean %˜BM = -0.5+0.5%. Conclusion: While GK practiced longer, they consumed similar amounts of fluid during practice and hydration measures were not significantly different than the FP. Overall, players reported euhydrated and maintained this status. An explanation for these results may be the continuous education and pre-season hydration measures (e.g., pre-post body mass measures) by the team`s athletic trainer, potentially impacting our results and supporting the role of athletic trainers in hydration education. Despite differences in practice time, GK and FP are similar in SR and hydration measures during pre-season practice. Athletic trainers should be aware of these similarities to minimize risk of dehydration. Future research should examine female soccer players at different competitive levels and during the season.